Studies on crossability among different varieties of Ananas comosus (L.) Merr. (Bromeliaceae) - Nisha, A. P.; Vijayan, Vrindha; Radhamany, P. M. (Current Botany, 2025)
Pineapple (Ananas comosus (L). Merr.) is a self incompatible plant. But hybridization is possible between different cultivars and varieties of pineapple. In the present study crossing experiments were carried out among different varieties of pineapple to assess the crossability among these varieties. In vitro pollen germination studies showed maximum pollen germination in A. comosus cv. MD2 in Brewbaker’s medium with 25% sucrose (85.57%). In self pollinated pistil, pollen grains were germinated on the stigma and penetrated into the style, but never grew deep into the style. After cross pollination, the pollen grains germinated on the stigmatic surface, penetrated and grow deep into the style. No seed set was observed in commercial cultivars after self pollination. But, a few seeds were produced in A. comosus var. bracteatus. In cross pollination experiments, seed set was observed in all crosses. The percentage of crossability and the number of seeds per fruitlet varied among different crosses. The cross between A. comosus cv. Mauritius female and A. comosus cv. Kew male showed maximum percentage of crossability and cross between A. comosus cv. MD2 female and A. comosus cv. Mauritius male produced the maximum number of seeds per fruitlet. The percentage of seed germination showed significant variation among the seeds produced from different crosses. The seedlings transferred to pots containing potting mixture showed vigorous growth.